Perceived Training Needs of Farmers about Dairy Farming in Karnataka : A Perspective of Farmers and Veterinarians - Balaraju, B.L.; Chander, Mahesh; Khandekar, Prakash; Rathod, Prakash Kumar (Indian Journal of Extension Education, 2013)
An ex-post-facto and exploratory study was conducted to assess the training needs of dairy farmers as perceived by them  and field veterinarians with a sample size of 120 dairy farmers and 66 field veterinarians in Davangere district of  Karnataka state. The training needs of dairy farmers in major six areas viz. breeding, feeding, health care, housing and  management, marketing & finance and dairy products preparation of dairy farming were assessed from the perspective of  farmers and veterinarians. In major areas of dairy farming, farmers perceived higher training needs in health care followed  by feeding and breeding while veterinarians perceived feeding as 'most important' area followed by health care and  breeding. Independent 't' test values indicate that veterinarians perceived higher extent of training needs for farmers in  dairy products preparation, feeding and health care. The study concluded that farmers and veterinarians perceived higher  extent of training needs in health care, feeding and breeding. Hence, the public and private extension agencies have to plan  effective extension strategy based on the perceived training needs of the farmers for improving the livestock productivity.
Keywords: Training needs; dairy farming; dairy farmer; field veterinarian